1995
DOI: 10.1288/00005537-199507000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cervical lymph node metastases in squamous cell carcinoma of the head and neck

Abstract: Although computed tomography and magnetic resonance imaging have contributed to the ability to identify metastatic disease in head and neck cancer, inadequacies in evaluating lymphadenopathy still exist. This study was undertaken to estimate the accuracy of radiological criteria used to detect cervical lymph node metastases. The morphological characteristics of 957 lymph nodes from 36 neck dissections from patients with squamous cell cancer were examined microscopically. A large number of malignant nodes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
101
3
5

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(114 citation statements)
references
References 19 publications
5
101
3
5
Order By: Relevance
“…Although it is believed that ECS occurs mainly in larger lymph nodes, some studies have identified ECS in lymph nodes as small as 2 mm. 52 Consistent with this observation, 12 of 186 (6%) patients with clinically negative neck dissections in the current study had histologic ECS in our pathologic review.…”
Section: Discussionsupporting
confidence: 87%
“…Although it is believed that ECS occurs mainly in larger lymph nodes, some studies have identified ECS in lymph nodes as small as 2 mm. 52 Consistent with this observation, 12 of 186 (6%) patients with clinically negative neck dissections in the current study had histologic ECS in our pathologic review.…”
Section: Discussionsupporting
confidence: 87%
“…The great challenge that is being faced by the head and neck oncologists and surgeons is the correct identification of the subset of head and neck cancer patients, of which oral carcinoma constitutes about 30% [90], without micro metastases to the cervical lymph nodes. Clinical palpation of the neck combined with the radiological investigative tools has not been able to correctly identify all these patients [39,102,130]. Despite the increase in knowledge and advancement in cancer management, there is still no method to determine correctly the real micro metastatic disease free neck.…”
Section: Justification Of the Studymentioning
confidence: 99%
“…Some large nodes may be inflammatory while some impalpable nodes may be carcinomatous [32,108]. Clinical palpation of the neck is not adequate for the correct identification of patients with neck node metastasis [39,102,130]. Factors such as neck fat thickness, neck stiffness or contraction, pain and swelling may affect the identification of neck node by palpation.…”
Section: Diagnosing the Node-negative Neckmentioning
confidence: 99%
See 2 more Smart Citations